2021
DOI: 10.1098/rstb.2019.0735
|View full text |Cite
|
Sign up to set email alerts
|

Queen loss increases worker survival in leaf-cutting ants under paraquat-induced oxidative stress

Abstract: Longevity is traded off with fecundity in most solitary species, but the two traits are positively linked in social insects. In ants, the most fecund individuals (queens and kings) live longer than the non-reproductive individuals, the workers. In many species, workers may become fertile following queen loss, and recent evidence suggests that worker fecundity extends worker lifespan. We postulated that this effect is in part owing to improved resilience to oxidative stress, and tested this hypothesis in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 88 publications
2
29
1
Order By: Relevance
“…Several studies have shown that reproductives live longer than non-reproductives even when they do not differ in ontogeny and morphology, e.g. as in certain species of ants [34,56,57] and reproducing workers of honeybees [58] and ants [37,40,43]. Similarly, highly fecund queens of Cardiocondyla ants live longer than queens that lay only a few eggs per week [59].…”
Section: Discussion (A) Remoulding Longevity and Fecundity In Social Animals: Causes And Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that reproductives live longer than non-reproductives even when they do not differ in ontogeny and morphology, e.g. as in certain species of ants [34,56,57] and reproducing workers of honeybees [58] and ants [37,40,43]. Similarly, highly fecund queens of Cardiocondyla ants live longer than queens that lay only a few eggs per week [59].…”
Section: Discussion (A) Remoulding Longevity and Fecundity In Social Animals: Causes And Consequencesmentioning
confidence: 99%
“…Majoe et al [37] report that increasing oxidative stress through treatment with paraquat increases the mortality of workers in three ant species. In two of them, this effect is less pronounced in queenless colonies, in which worker reproduction is generally induced, than queenright colonies, where workers typically do not lay eggs.…”
Section: Contributionsmentioning
confidence: 99%
“…Here our focus is on social insects, among which experimentally induced ROS increase senescence of social bees and ants [6][7][8][9]. One effect of ROS is the oxidation of amino acids in proteins by introducing carbonyl groups, which often leads to a loss of catalytic activity and simultaneously marks the protein for proteolytic degradation (reviewed in [10] and [11]).…”
Section: (A) Oxidative Stressmentioning
confidence: 99%
“…Past research indicated that the longevity of workers decreased with prolonged queenlessness in the field experiment [29]. On the other hand, queenlessness expanded the worker longevity and reproductivity of bees [5,9,10] and ants [30], but only when the queens were absent at the worker larval stage. Hence, the presence of a queen affects longevity of workers in different ways depending on whether the queen is present at their larval or imago stage.…”
Section: Discussionmentioning
confidence: 99%